Prosedur Create Sales Order and Delivery Order Use System Application and Product in Data Processing (SAP) on PT. Central Proteina Prima Tbk - Ekkiwinatha, Novan; Pratiwi, Annissa; Febrianti, Dian; Benazhier Fitrah, Bunga (Review of Accounting and Taxation, 2024)
This study aims to explain the procedure for creating sales orders and delivery orders using the system application and product in data processing (SAP) application. The research design used in the preparation of this Final Project is a descriptive qualitative design, which is a research approach that focuses on natural phenomena or symptoms in the field. The data used in the preparation of this Final Project was obtained from direct interviews with related parties at PT Central Proteina Prima Tbk - Anyer Hatchery, and documentation / archives regarding the SAP application used by the company, especially in the create sales order and delivery order procedures. The results of the research conducted show that PT Central Proteina Prima Tbk - Anyer Hatchery has weaknesses in the authorization process in the Standard Operating Procedure (SOP) related to creating sales orders and delivery orders, especially in the CNPD division. But basically, the SAP system has strongly emphasized the importance of the distribution of authorizations as part of the internal control system (SPI) that must be carried out by the company. Therefore, the implementation of SPI and standard operating procedures (SOP) must be better implemented properly and correctly so that business continuity can run more optimally.